Transformative Leadership: Exploration of the Combination of Christian Values and Technological Advances in the Digital Era : Kepemimpinan Transformatif: Eksplorasi Perpaduan Nilai-nilai Kristen dan Kemajuan Teknologi di Era Digital - Sanjaya, Yudhy (IAKN TORAJA, 2024)
Abstract: The integration of Christian values with technological advances in Christian leadership practice is a relevant challenge in today's digital era. This research aims to explore this combination and identify practical strategies and implications in the context of Christian leadership theory and practice. The research method used is literature analysis and qualitative data collection through literature study. The research results show that, although there is conflict between Christian values and technological advances, there are also opportunities to utilize technology as a tool for strengthening community and spiritual growth. The implications of this research are the need for further research on practical strategies for overcoming these conflicts, longitudinal studies to understand the development of Christian leadership practices in adopting new technology, as well as research on how transformative Christian leadership can influence spiritual and community growth in the long term. Thus, this research makes a significant contribution to the development of Christian leadership theory and practice in the digital era. Keywords: Christianity, digital era, leadership, technology, transformative. Abstrak: Integrasi nilai-nilai Kristen dengan kemajuan teknologi dalam praktik kepemimpinan Kristen merupakan tantangan yang relevan di era digital saat ini. Penelitian ini bertujuan untuk mengeksplorasi perpaduan tersebut dan mengidentifikasi strategi praktis serta implikasi dalam konteks teori dan praktik kepemimpinan Kristen. Metode penelitian yang digunakan adalah analisis literatur dan pengumpulan data kualitatif melalui studi pustaka. Hasil penelitian menunjukkan bahwa, meskipun terdapat konflik antara nilai-nilai Kristen dan kemajuan teknologi, terdapat juga peluang untuk memanfaatkan teknologi sebagai alat untuk memperkuat komunitas dan pertumbuhan rohani. Implikasi penelitian ini adalah perlunya penelitian lebih lanjut tentang strategi praktis untuk mengatasi konflik tersebut, studi longitudinal untuk memahami perkembangan praktik kepemimpinan Kristen dalam mengadopsi teknologi baru, serta penelitian tentang bagaimana kepemimpinan Kristen yang transformatif dapat memengaruhi pertumbuhan rohani dan komunitas dalam jangka panjang. Dengan demikian, penelitian ini memberikan kontribusi yang signifikan bagi pengembangan teori dan praktik kepemimpinan Kristen di era digital. Kata Kunci: era digital, kepemimpinan, kristen, teknologi, transformatif.